Effects of rumen-escape lipid in a range supplement on postpartum reproductive function in beef cows - R.B. Hightshoe; R.C. Cochran; L.R. Corah; D.L. Harmon; G.H. Kiracofe (Kansas Agricultural Experiment Station Research Reports, 1990)
Postpartum cows receiving a range supplement containing rumen-escape lipid exhibited altered hormone and cholesterol levels compared to cows not fed lipid. Sixty-seven percent of lipid-fed cows exhibited a normal (18.2 d) first estrous cycle vs 33% for cows not receiving lipid. Incorporation of rumen-escape lipid into range supplements appears to significantly improve postpartum reproductive characteristics.
Keywords: Cattlemen' s Day; 1990; Kansas Agricultural Experiment Station contribution; no. 90-361-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 592; Beef; Rumen-escape lipid; Estrous cycle; Cholesterol; Postpartum